ANALISIS GAYA BAHASA PADA ANTOLOGI LIRIK â€œBINGUNGâ€ KARYA IKSAN SKUTER - farhan refiandika; ika mustika; enung nurhayati (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The study is based on the unique nature of each creation of lyrics that contain both intrinsic and extrinsic elements in each line. The goal of this research isn't to analyze the language style on a dazed lyric antology book by icsan scooter. Researchers analyze the lyrics using a descriptive approach. The source of the data used by researchers is that of 5 lyrics from a total of 60 lyrics. Researchers focused 6 figures of speech on the study: metaphor, personification, hyperbole, anafora, epistrophur and asonansi. Research data is summed up: (1) lyrics with the most grammatical usage are those that are entitled confused with a total of 25 different language styles. The lyrics with the least grammatical usage are those titled shankara with a total of 9 different language styles. (2) the metaphorical style is 11, as many as 10 personified, 11 of hyperbole, anafora as many as 8, epistrofa as 4, and 23 as of assonance. With a total of 67 figures of speech on the five lyrics that have been analyzed.